Zathura - Jon, Favreau; Koepp, David; Kamps, John (Sony Pictures Home Entertainment ; distributed in the Philippines by MagnaVision, 2005)
Danny twists the key of an old science fiction game. The game unleashes a localized meteor shower and wrenches Danny's house into orbit around a distant ringed planet. Besides Danny, his brother Walter and sister Lisa have to go along. Soon a defective robot, a rangy astronaut, and an alien spaceship enter the picture. The only way the kids can return their house to its proper space-time coordinates is to finish the game, but before they can finish, the game board falls into the hands of some rather nasty, carnivorous lizards.